Active sites and deactivation of room temperature CO oxidation on Co3O4 catalysts: combined experimental and computational investigations. (31st August 2022) - Yigit, Nevzat; Genest, Alexander; Terloev, Schamil; Möller, Jury; Rupprechter, Günther
Abstract: Co3 O4 is a well-known low temperature CO oxidation catalyst, but it often suffers from deactivation. We have thus examined room temperature (RT) CO oxidation on Co3 O4 catalysts by operando DSC, TGA and MS measurements, as well as by pulsed chemisorption to differentiate the contributions of CO adsorption and reaction to CO2 . Catalysts pretreated in oxygen at 400 °C are most active, with the initial interaction of CO and Co3 O4 being strongly exothermic and with maximum amounts of CO adsorption and reaction. The initially high RT activity then levels-off, suggesting that the oxidative pretreatment creates an oxygen-rich reactive Co3 O4 surface that upon reaction onset loses its most active oxygen. This specific active oxygen is not reestablished by gas phase O2 during the RT reaction. When the reaction temperature is increased to 150 °C, full conversion can be maintained for 100 h, and even after cooling back to RT. Apparently, deactivating species are avoided this way, whereas exposing the active surface even briefly to pure CO leads to immediate deactivation. Computational modeling using DFT helped to identify the CO adsorption sites, determine oxygen vacancy formation energies and the origin of deactivation. A new species of CO bonded to oxygen vacancies at RT was identified, which may block a vacancy site from further reaction unless CO is removed at higher temperature. The interaction between oxygen vacancies was found to be small, so that in the active state several lattice oxygen species are available for reaction in parallel.